Complex Digital Circuits - Deschamps, Jean-Pierre; Valderrama, Elena; Terés, Lluís (Springer International Publishing : Imprint: Springer, 2019)
This textbook is designed for a second course on digital systems, focused on the design of digital circuits. It was originally designed to accompany a MOOC (Massive Open Online Course) created at the Autonomous University of Barcelona (UAB), currently available on the Coursera platform. Readers will learn to develop complex digital circuits, starting from a functional specification, will know the design alternatives that a development engineer can choose to reach the specified circuit performance, and will understand which design tools are available to develop a new circuit. Provides textbook coverage for one-semester, second course on digital systems, focused on the design of digital circuits; Explains how to develop complex digital circuits, starting from a functional specification; Demonstrates which design tools are necessary to develop a new circuit; Describes the main problems development engineers are faced with, during the process of developing a new circuit; Uses applied examples of complex circuits, such as elliptic curve scalar product, image processing, finite field operations; Includes numerous, solved-examples in-text, as well as end of chapter exercises; Provides all necessary VHDL and C source files.